Bond strength of ceramic inlay with dental hard tissues depending on the type of adhesive system used – review of literature - Rączkiewicz, Magdalena; Mazurek, Karolina; Mierzwińska-Nastalska, Elżbieta (Journal of Stomatology, 2016)
Reconstruction of dental hard tissues with the use of inlays results in very good aesthetic and functional effects. Indirect prosthetic reconstruction in the form of an inlay requires preparation of the tooth structure to ensure retention and proper distribution of forces in the cavity. Adhesion of ceramic restorations to enamel and dentine is possible due to the incorporation of resin monomer into the hard tissues. This linkage can be provided by adhesive systems, which are divided according to the application technology used into etch-and-rinse and self-etch systems. The purpose of this literature review is to summarise the latest and the most reliable study results on the leakage of the adhesive connection of ceramics with dental hard tissues. Electronic research of the most relevant articles was conducted in English in the MEDLINE database with access via PubMed. Among the publications available in the MEDLINE database, those published in the years 2001-2016 were analyzed in order to select the most modern materials and methods. The search was based on the following keywords: adhesives, bonding, cements, ceramics, dental porcelain, inlay, microleakage, self-adhesive. All the analyzed articles present the description of in vitro study and relate to the comparison of etch-and-rinse and self-etching systems. Based on this analysis, it can be concluded that the most efficient bonding of hard tissues with the tooth can be achieved using etch-and-rinse systems. Self-adhesive systems preceded by the procedure of selective etching of enamel enable the achievement of a similar quality of the bonding obtained when using the etch-and-rinse systems. In addition, while using self-adhesive systems, special care should be taken not to overdry dentine during the cementation procedure. The type of ceramic does not affect the quality of the obtained bonding; moreover, processes of stimulated aging have no statistically significant effect on the formation of microleakage in in vitro studies.